Evaluating crude whey for bioethanol production using non-Saccharomyces yeast, Kluyveromyces marxianus - TOKSOY ÖNER, EBRU (SPRINGER INTERNATIONAL PUBLISHING AG, 2021)
Ethanol production from non-food substrate is strongly recommended to avoid competition with food production. Whey, which is rich in nutrients, is one of the non-food substrate for ethanol production by Kluyveromyces spp. The purpose of this study was to optimize ethanol from different crude (non-deproteinized, non-pH adjusted, and non-diluted) whey using K. marxianus ETP87 which was isolated from traditional yoghurt. The sterilized and non-sterilized whey were employed for K. marxianus ETP87 substrate to evaluate the yeast competition potential with lactic acid and other microflora in whey. The effect of pH and temperature on ethanol productivity from whey was also investigated. Peptone, yeast extract, ammonium sulfate ((NH4)(2)SO4), and urea were supplemented to whey in order to investigate the requirement of additional nutrient for ethanol optimization. The ethanol obtained from non-sterilized whey was slightly and statistically lower than sterilized whey. The whey storage at 4 degrees C didn't guarantee the constant lactose presence at longer preservation time. Significantly high amount of ethanol was attained from whey without pH adjustment (3.9) even if it was lower than pH controlled (5.0) whey. The thermophilic yeast, K. marxianus ETP87, yielded high ethanol between 30 and 35 degrees C, and the yeast was able to produce high ethanol until 45 degrees C, and significantly lower ethanol was recorded at 50 degrees C. The ammonium sulfate and peptone enhanced ethanol productivity, whereas yeast extract and urea depressed the yeast ethanol fermentation capability. The K. marxianus ETP87, the yeast isolated from traditional yoghurt, is capable of producing ethanol from non-sterilized and non-deproteinized substrates.
Keywords: Bioethanol; Whey; Kluyveromyces marxianus; Lactose; High-temperature ethanol; CHEESE WHEY; ETHANOL-PRODUCTION; FERMENTATION; BATCH; LACTOSE